Decentralization and service delivery - Aḥmad, Junaid; World Bank. ([Washington, D.C. : World Bank, 2005)
"Dissatisfied with centralized approaches to delivering local public services, a large number of countries are decentralizing responsibility for these services to lower-level, locally elected governments. The results have been mixed. The paper provides a framework for evaluating the benefits and costs, in terms of service delivery, of different approaches to decentralization, based on relationships of accountability between different actors in the delivery chain. Moving from a model of central provision to that of decentralization to local governments introduces a new relationship of accountability-between national and local policymakers-while altering existing relationships, such as that between citizens and elected politicians. Only by examining how these relationships change can we understand why decentralization can, and sometimes cannot, lead to better service delivery. In particular, the various instruments of decentralization-fiscal, administrative, regulatory, market, and financial-can affect the incentives facing service providers, even though they relate only to local policymakers. Likewise, and perhaps more significantly, the incentives facing local and national politicians can have a profound effect on the provision of local services. Finally, the process of implementing decentralization can be as important as the design of the system in influencing service delivery outcomes. "--World Bank web site.
Title from PDF file as viewed on 5/13/2005.
Includes bibliographical references.
Also available in print.
Keywords: Decentralization in government; Municipal services